Rattan Craft Industry Development Strategy in the Study of Maqashid Syariah in Tanjung Pasir Village - Syahputra, Jodi; Ramadhani, Sri; Tambunan, Khairina (Electronic Journal of Education, Social Economics and Technology, 2025)
The rattan craft industry in Tanjung Pasir Village, North Labuhanbatu Regency, has great economic potential. However, this industry faces various challenges, such as limited market access, competition with imported products, and limited capital and raw materials. This study aims to analyze the development strategy of the rattan craft industry based on the principles of Maqashid Sharia. This study uses a qualitative approach with data collection techniques in the form of field observations, in-depth interviews, and literature studies. This method was chosen to obtain a comprehensive understanding of the real conditions of the rattan craft industry and its development strategies within the Maqashid Sharia framework. The results of the study indicate that industrial development can be carried out through improving entrepreneur skills, utilizing technology, and implementing Maqashid Sharia values, such as Hifz al-Mal in financial management and Hifz an-Nafs in efforts to improve entrepreneur welfare. This strategy is expected to encourage the growth of the rattan industry in a sustainable manner in accordance with the principles of Maqashid Sharia.